Pharmacological Treatment of Ascites: Challenges and Controversies - Jimmy Che-To Lai; Junlong Dai; Lilian Yan Liang; Grace Lai-Hung Wong; Vincent Wai-Sun Wong; Terry Cheuk-Fung Yip (Pharmaceuticals)
Ascites is the most common complication from cirrhosis related to portal hypertension and depicts the onset of hepatic decompensation. Ranging from uncomplicated to refractory ascites, the progression carries prognostic value by reflecting the deterioration of underlying cirrhosis and portal hypertension. Diuretics have been the mainstay of treatment to control ascites, but the side effects heighten when the dosage is escalated. Non-selective beta-blockers (NSBBs) are widely used nowadays to prevent hepatic decompensation and variceal hemorrhage. However, with worsening systemic vasodilation and inflammation when ascites progresses, patients on NSBBs are at risk of hemodynamic collapse leading to renal hypoperfusion and thus hepatorenal syndrome. Long-term albumin infusion was studied to prevent the progression of ascites. However, the results were conflicting. Sodium-glucose cotransporter-2 inhibitors are under investigation to control refractory ascites. With that, patients with refractory ascites may require regular large-volume paracentesis. With an aging population, more patients are put on anti-thrombotic agents and their risks in decompensated cirrhosis and invasive procedures have to be considered. In general, decompensated cirrhosis with ascites poses multiple issues to pharmacological treatment. In the present review, we discuss the challenges and controversies in the pharmacological treatment of ascites.